Safety and efficacy of transvenous lead extraction using mechanical (non-laser) extraction tools. (19th May 2022) - Oconnor, M; Schmid, P; Knoll, K; Schaarschmidt, C; Bock, M; Bahlke, F; Georgi, M; Froehlich, R; Kottmaier, M; Reents, T; Bourier, F; Hessling, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The rate of transvenous lead extraction (TLE) is increasing with an increasing rate of complex devices being implanted. TLE is now a routine part of cardiac device management and up to date data on the safety and efficacy of TLE with modern tools and techniques is essential to management decisions regarding non-infectious indications for lead extraction. Purpose: To evaluate the safety and efficacy of TLE in a contemporary cohort using mechanical (non-laser) extraction tools. Methods: We present a contemporary, prospective review of TLE at our high-volume cardiac centre. All patients undergoing TLE from June 2016 and June 2019 were enrolled in our local database and baseline clinical data, procedural information and outcome data were collected. Results: In total 561 leads were explanted (n=153) or extracted (n=408) from 341 patients over the study period. Patients were predominantly male (71%) with a mean age of 65 ± 17 years. The most common indication for lead removal was lead failure (45.2%, n=154) followed by infection of the pocket or device (29.3%, n=100). The mean dwell time of the 408 extracted leads was 7.2 years; 35% had a dwell time of 5-10 years, 23% had a dwell time >10 years and 4% had a dwell time >20 years (Figure 1). In total, complete success was achieved in 96.4% (n=541) leads, clinical success in a further 2.1% (n=12) and failure only in 1.4% (n=8). Clinical success was high (93%) even in leads with dwell time >20 years (Figure 2). There was an overall complication rate of 0.9% (3/341) for major complications and 1.5% (5/341) for minor complications. There were no deaths. Conclusions: Our data would suggest that there are ongoing improvements in the safety profile and success rates of lead extraction undertaken by experienced operators now with a major complication rate of <1%.